Extremely Rapid Spread of Human Immunodeficiency Virus Type 1 BF Recombinants in Argentina - Aulicino, Paula (2007)
The epidemic of human immunodeficiency virus type 1 (HIV-1) in Argentina is distinctive in that many infections are caused by subtype BF recombinant viruses. To determine their demographic history, we estimated the evolutionary rate, mode of population growth, and age of genetic diversity among 40 BF vpu sequences. This revealed one of the highest substitution rates reported for HIV-1, at 10.793 x 10(-3) substitutions per site per year, and a very rapid rate of population growth, with an initial mean epidemic doubling time of 3.72 months. This rapid population growth is compatible with an elevated fitness for subtype BF compared to that for "pure" B and F viruses.